Triiodothyronine Facilitates Weaning From Extracorporeal Membrane Oxygenation by Improved Mitochondrial Substrate Utilization - Files, Matthew D. (Blackwell Publishing Ltd, 2014)
BACKGROUND: Extracorporeal membrane oxygenation (ECMO) provides a bridge to recovery after myocardial injury in infants and children, yet morbidity and mortality remain high. Weaning from the circuit requires adequate cardiac contractile function, which can be impaired by metabolic disturbances induced either by ischemia‐reperfusion and/or by ECMO. We tested the hypothesis that although ECMO partially ameliorates metabolic abnormalities induced by ischemia‐reperfusion, these abnormalities persist or recur with weaning. We also determined if thyroid hormone supplementation (triiodothyronine) during ECMO improves oxidative metabolism and cardiac function. METHODS AND RESULTS: Neonatal piglets underwent transient coronary ischemia to induce cardiac injury then were separated into 4 groups based on loading status. Piglets without coronary ischemia served as controls. We infused into the left coronary artery [2‐(13)C]pyruvate and [(13)C(6), (15)N]l‐leucine to evaluate oxidative metabolism by gas chromatography‐mass spectroscopy and nuclear magnetic resonance methods. ECMO improved survival, increased oxidative substrate contribution through pyruvate dehydrogenase, reduced succinate and fumarate accumulation, and ameliorated ATP depletion induced by ischemia. The functional and metabolic benefit of ECMO was lost with weaning, yet triiodothyronine supplementation during ECMO restored function, increased relative pyruvate dehydrogenase flux, reduced succinate and fumarate, and preserved ATP stores. CONCLUSIONS: Although ECMO provides metabolic rest by decreasing energy demand, metabolic impairments persist, and are exacerbated with weaning. Treating ECMO‐induced thyroid depression with triiodothyronine improves substrate flux, myocardial oxidative capacity and cardiac contractile function. This translational model suggests that metabolic targeting can improve weaning.